COVID-19 associated rhino-orbital-cerebral mucormycosis: An observational study from Eastern India, with special emphasis on neurological spectrum. Issue 5 (September 2021) - Dubey, Souvik; Mukherjee, Debaleena; Sarkar, Peyalee; Mukhopadhyay, Pradip; Barman, Debasis; Bandopadhyay, Manimoy; Pandit, Alak; Sengupta, Amitabha; Das, Sudip; Ghosh, Soumitra; Adhikari, Souvik; Biswas, Partha Sundar; et al.
Abstract: Aims: 1: Describe the epidemiology and determine risk factors for COVID-19 associated mucormycosis. 2: Elaborate the clinical spectrum of Rhino-Orbital-Cerebral Mucormycosis (ROCM), pattern of neuroaxis involvement and it's radiological correlates. Methods: Observational study. Consecutive, confirmed cases of mucormycosis (N = 55) were included. A case of mucormycosis was defined as one who had clinical and radiological features consistent with mucormycosis along with demonstration of the fungus in tissue via KOH mount/culture/histopathological examination (HPE). Data pertaining to epidemiology, risk factors, clinico-radiological features were analysed using percentage of total cases. Results: Middle aged, diabetic males with recent COVID-19 infection were most affected. New onset upper jaw toothache was a striking observation in several cases. Among neurological manifestations headache, proptosis, vision loss, extraocular movement restriction; cavernous sinus, meningeal and parenchymal involvement were common. Stroke in ROCM followed a definitive pattern with watershed infarction. Conclusions: New onset upper jaw toothache and loosening of teeth should prompt an immediate search for mucormycosis in backdrop of diabetic patients with recent COVID-19 disease, aiding earlier diagnosis and treatment initiation. Neuroaxis involvement was characterized by a multitude of features pertaining to involvement of optic nerve, extraocular muscles, meninges, brain parenchyma and internal carotid artery. Highlights: ROCM results from simultaneous occurrence of different risk factors: diabetes > COVID-19> steroid > occupational exposure. Neurological manifestations are prevalent in ROCM and associated with poor prognosis despite therapy. Upper jaw tooth pain/loosening is a potential heralding sign of ROCM. Radiological changes preceding clinical features underscore the role of imaging for early diagnosis and treatment.